(3JPcQI GdabgGAs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3GdaUd GdKGfi ai HjY GdfbO hGfSHI hGdSda hajg eWdHGf s
(3BNQgG (B:s
(3EPG cGf GdeGd ai jOg abhdGf hefge ef bd JbH bhdkG hGMOkG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B390s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B(372 (3N(B) s
Keywords: (3abg GdePGgH GdCNQis